Conductivity Performance of Biopolymer Membrane based on Kappa-Carrageenan - Zakaria, Rosnah; Mohd Nor, Asiah; Kartini Jaafar, Nor; Malik Marwan Ali, Ab (International Journal of Engineering and Technology, 2019)
Smart energy systems are well-known among researchers who wish to introduce new technology. Biopolymer is an environmentally friendly material. Kappa-Carrageenan is one type of biopolymer with high proton conductivity and durability which has been studied for almost 10 years. The membrane based on kappa-carrageenan was prepared using solution cast technique incoorperated with ammonium thiocyanate (NH4SCN). The solution was poured into glass petri dishes and left to dry at room temperature before further dying in an oven at 60Â°C to obtain thin films. The highest conductivity was obtained for 40 wt. % NH4SCN added kappa-carrageenan. The conductivity dropped when the amount of kappa-carrageenan is equal to the amount of NH4SCN. The maximum conductivity of kappa-carrageenan incorporated with NH4SCN obtained is 1.64E-03 S cm-1. FTIR studies show peak at 1638 cm-1 in pure kappa-carrageenan which slowly disappeared at 60 wt. % kappa-carrageenan. It is however characterized by a peak attributed to NH4SCN at 1600 cm-1 which appeared for 50 wt. % of kappa-carrageenan and below.Â Â